Complicated acute frontal sinusitis in a child presenting with acute ischemic stroke. (April 2021) - Davison, Wesley L.; Gudis, David A.
Abstract: Acute stroke as a complication of sinusitis is exceedingly rare, and even more so in children. Here we present the case of a healthy 9-year-old male who had an acute stroke in the setting of severe acute pansinusitis. The patient was started on parenteral antibiotics and underwent urgent endoscopic sinus surgery and adenoidectomy, ultimately making a full neurologic recovery. Of the previously reported cases of stroke as a complication of sinusitis, all showed evidence of carotid artery pathology. This is the first report to our knowledge of acute sinusitis presenting as stroke with normal arterial anatomy and function.